Power, Knowledge and Feminist Scholarship An Ethnography of Academia - Pereira, Maria do Mar (Taylor & Francis, 2017)
Feminist scholarship is sometimes dismissed as not quite 'proper' knowledge - it's too political or subjective, many argue. But what are the boundaries of 'proper' knowledge? Who defines them, and how are they changing? How do feminists negotiate them? And how does this boundary-work affect women's and gender studies, and its scholars' and students' lives? These are the questions tackled by this ground-breaking ethnography of academia inspired by feminist epistemology, Foucault, and science and technology studies. Drawing on data collected over a decade in Portugal and the UK, US and Scandinavia, this title explores different spaces of academic work and sociability, considering both official discourse and 'corridor talk'. It links epistemic negotiations to the shifting political economy of academic labour, and situates the smallest (but fiercest) departmental negotiations within global relations of unequal academic exchange.